2002
DOI: 10.1023/a:1021173124640
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This is the first report of two successful 100 l scale transienttransfections in a standard stirred bioreactor. More than half a gram of a monoclonal antibody (IgG) were produced in less than 10 days using a technology called large-scale transient gene expression(LS-TGE). Suspension adapted HEK 293 EBNA SF cells were transfectedwithin a 150 l (nominal) bioreactor by a modified calcium phosphateco-precipitation method with more than 75 mg of plasmid DNA per run.A mixture of three different plasmids, one encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Increasing the shaking or stirring speed could control the size of cell aggregates [32], but enhanced shear stress would also lead to lower cell viability in suspension culture. Some researchers have reported that the chelation of extracellular Ca 2+ induced disassembly of tight and adherent junctions [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the shaking or stirring speed could control the size of cell aggregates [32], but enhanced shear stress would also lead to lower cell viability in suspension culture. Some researchers have reported that the chelation of extracellular Ca 2+ induced disassembly of tight and adherent junctions [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…While large-scale TGE has been carried out in a variety of instrumented and noninstrumented cultivation vessels, the largest transfection reported to date has been in a 150-L stirred tank bioreactor with a working volume of 110 liters with HEK 293 cells (104). The largest transfection with CHO cells has been 80 L (99).…”
Section: Cultivation Vesselsmentioning
confidence: 99%
“…The largest transfection with CHO cells has been 80 L (99). Overall, secreted r-protein yields in the range of 2-22 mg/L have been achieved in instrumented bioreactors ranging in nominal volume from 3-to 150-l using either batch or fed-batch approaches with either HEK 293 or CHO cells (83,94,96,99,104). The Wave bioreactor with disposable plastic bags has also proven to be well-suited for TGE with the largest volume reported to be 10 L with cultures of HEK 293 cells (105).…”
Section: Cultivation Vesselsmentioning
confidence: 99%
“…However, fairly large amounts of plasmid DNA are needed for the transient transfection of bioreactors at large scale [41]. Under such circumstances the efficiency of the DNA transfection as well as the cost of the plasmid are of major concern, while the purity of the plasmid per se is only of secondary importance as long as an adverse effect of the putative impurities (toxicity, introduction of adventitious agents) can be excluded.…”
Section: Transient Transfection Of Cho Cellsmentioning
confidence: 99%
“…The methods of choice for the transient transfection used in our laboratory are the DNA-calcium phosphate coprecipitation technique [41] and the Lipofectamine 2000 method (GibcoBRL). It was not possible to use the calcium phosphate transfection protocol with plasmid DNA still linked to the AML (protein expression was unsatisfactory, data not shown).…”
Section: Transient Transfection Of Cho Cellsmentioning
confidence: 99%